Gold-catalyzed cyclizations: a comparative study of ortho,ortho′-substituted KITPHOS monophosphines with their biaryl monophosphine counterpart SPHOS - Hashmi, A. Stephen K.; Loos, Annette; Doherty, Simon; Knight, Julian G.; Robson, Katharine J.; Rominger, Frank (Advanced synthesis & catalysis, 2011)
Electrophilic gold(I) triflimide (trifluoromethanesulfonimide) complexes of electron-rich ortho,ortho′-disubstituted KITPHOS (11-dicyclohexylphosphino-12-phenyl-9,10-ethenoanthracene) monophosphines are efficient catalysts for intramolecular cycloisomerizations that afford phenols, 3-acylindenes and methylene-oxazolines; comparative catalyst testing showed that these catalysts either competed with or outperformed that based on SPHOS [2-(2′,6′-dimethoxybiphenyl)dicyclohexylphosphine]. An electron-rich biarylmonophosphine containing a single ortho-methoxy substituent, prepared by rhodium-catalyzed [2+2+2] cycloaddition between a 1-alkynyl(dicyclohexylphosphine) oxide and 1,7-octadiyne, also formed a highly efficient catalyst for the same transformations. Monitoring of comparative catalyst testing between a KITPHOS-based gold(I) triflimide complex containing a coordinated tetrahydrothiophene and its counterpart coordinated solely by the triflimide anion revealed that the former is an order of magnitude less efficient than the latter, confirming that tetrahydrothiophene can be an effective catalyst inhibitor.